LZTR1 loss-of-function variants associated with café au lait macules with or without freckling - Horn, Svea; Neuhann, Teresa; Hennig, Corina; Abad-Perez, Angela; Prott, Eva-Christina; Cardellini, Lisa; Potratz, Cornelia; Leubner, Jonas; Eichhorn, Birgit; Merkel, Martin; Abicht, Angela; Kaindl, Angela M. (Frontiers in Neurology, 2024)
Pathogenic variants in the leucine zipper-like transcriptional regulator 1 gene (LZTR1) have been identified in schwannomatosis and Noonan syndrome. Here, we expand the phenotype spectrum of LZTR1 variants. We identified four loss-of-function heterozygous LZTR1 variants in five children with multiple café au lait macules and one adult with multiple café au lait macules and axillar freckling, by applying gene panel analysis in four families. The three LZTR1 variants, namely, c.184del/p.Glu62Serfs*39, c.1927C < T/p.Gln643*, and c.857_858delinsT/p.Gly286Valfs*65, were novel, whereas the variant c.1018C > T/ p.Arg340* had been previously reported in a patient with schwannomatosis. Similar to what is known from other LZTR1-associated conditions, penetrance of the skin manifestations was reduced in two carriers of the familial variants. Our study expands the LZTR1 phenotype to the presence of isolated café au lait macules with or without freckling. Thus, variants in the LZTR1 gene should be considered in patients with multiple café au lait macules.